Biodiversity responses to land-use and restoration in a global biodiversity hotspot: Ant communities in Brazilian Cerrado - Dalle Laste, Keila Caroline [UNESP]; Durigan, Giselda; Andersen, Alan N. (Wiley, 2019)
Given that land-use change is the main cause of global biodiversity decline, there is widespread interest in adopting land-use practices that maintain high levels of biodiversity, and in restoring degraded land that previously had high biodiversity value. In this study, we use ant taxonomic and functional diversity to examine the effects of different land uses (agriculture, pastoralism, silviculture and conservation) and restoration practices on Cerrado (Brazilian savanna) biodiversity. We also examine the extent to which ant diversity and composition can be explained by vegetation attributes that apply across the full land management spectrum. We surveyed vegetation attributes and ant communities in five replicate plots of each of 13 land-use and restoration treatments, including two types of native vegetation as reference sites: cerrado sensu stricto and cerradão. Several land-use and restoration treatments had comparable plot richness to that of the native reference habitats. Ant species and functional composition varied systematically among land-use treatments following a gradient from open habitats such as agricultural fields to forested sites. Tree basal area and grass cover were the strongest predictors of ant species richness. Losses in ant diversity were higher in land-use systems that transform vegetation structure. Among productive systems, therefore, uncleared pastures and old pine plantations had similar species composition to that occurring in cerrado sensu stricto. Restoration techniques currently applied to sites that were previously Cerrado have focused on returning tree cover, and have failed to restore ant communities typical of savanna. To improve restoration outcomes for Cerrado biodiversity, greater attention needs to be paid to the re-establishment and maintenance of the grass layer, which requires frequent fire. At the broader scale, conservation planning in agricultural landscapes, should recognize the value of land-use mosaics and the risks of homogenization.
Keywords: biodiversity conservation; functional composition; land mosaic; savanna; species richness